Preconditions for Post-Employment Learning: Preliminary Results from Ongoing Research - Salter, Linda (International Review of Research in Open and Distributed Learning, 2011)
This article describes the first phase of a two-phase, mixed-method study. The study, now in progress, explores how and to what extent willingness to engage in learning in mature adulthood is influenced by prior experiences and specific individual personality variables, such as perceived locus of control and degree of self-efficacy. Study participants in this phase are 20 active adults over the age of 50 who participate in various formal and informal programs at a YMCA in a suburb of Seattle, Washington. Preliminary results thus far are discussed with respect to how they may inform educators of mature adults in open education settings. A profile of the characteristics of mature adults likely to be engaged in learning activities is beginning to emerge. A larger sample of participants taken from the same population is now being studied to confirm or refute the value of this profile.